Teaching Reading Comprehension Using Numbered Heads Together To The Third Year Student Of SMP Negeri 2 Boyolali - Wijayanti, Intan (2012)
This study is aimed at describing the technique of teaching reading comprehension using Numbered Heads Together, the problem faced by the students, and the solution made by the teacher. the research was conducted at SMP Negeri 2 Boyolali, the result of this study is intended to give contribution to the teaching learning English of reading. The data of the research are information about technique of teaching reding comprehension using Numbered Heads Together. The sources of the data are the activities in the teaching-learning reading comprehension, informants which are the English teacher and the students, and the documents which are formed in syllabus and the lesson plan. Based on the research finding, it can be concluded that the method of Numbered Heads Together was very helpful to the teacher. The students became very attracted in joining the lesson. The technique of Numbered Heads Together also built cooperation and convidence during the teaching-learning activites. The weaknesses of this method are students became noisy and had envied feelings to other because the visibility of the teacher during the game was limited.